2022
DOI: 10.1021/acs.organomet.2c00138
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycarbonylation of Alkenes with Formic Acid Catalyzed by a Rhodium(III) Hydride Diiodide Complex Bearing a Bidentate Phosphine Ligand

Abstract: An improved catalytic system was developed for the Rh complexcatalyzed hydroxycarbonylation of alkenes using formic acid (HCOOH). Ligand screening revealed DPEphos, a bidentate phosphine ligand, to be effective, and the corresponding rhodium(III) hydride diiodide complex, RhHI 2 (CO)(DPEphos) (2), was applied as a catalyst. Complex 2 showed high activity and selectivity in the hydroxycarbonylation of alkenes using HCOOH without any additives and was applicable to a variety of alkene substrates. Analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…We therefore investigated the effect of different natural bite angles of the diphosphine ligands varying from 83° to 114°. 21 As we can be seen from Table 1, there was a significant positive correlation between bite angle and reaction yield. Yields improved as the increasing bite angle of the diphosphine ligands increased and nixantphos (114°) gave the desired product in 95% yield (Table 1, entry 19).…”
mentioning
confidence: 71%
“…We therefore investigated the effect of different natural bite angles of the diphosphine ligands varying from 83° to 114°. 21 As we can be seen from Table 1, there was a significant positive correlation between bite angle and reaction yield. Yields improved as the increasing bite angle of the diphosphine ligands increased and nixantphos (114°) gave the desired product in 95% yield (Table 1, entry 19).…”
mentioning
confidence: 71%
“…Moreover, the chelating effect of the diphosphine ligands is crucial to the thermal stability of the palladium intermediate. Therefore, the effect of different natural bite angles of the diphosphine ligands, which ranged from 83° to 114°, [18a] was studied. As shown in Table 1, there is a direct correlation between the bite angle and the yield of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent some drawbacks associated with CO gas, efforts have also been made for the development of hydrocarboxylation with nongaseous CO surrogates . For example, we and others , have shown that hydrocarboxylation can be achieved with HCO 2 H under mild conditions assisted with HCO 2 Ar or Ac 2 O. , Readily available oxalic acid could also serve as a potential carbonyl source for the hydrocarboxylation of olefins with a possible distinct reaction mechanism, which could provide new opportunities to regulate the reactivity and selectivity. The hydrocarboxylation of olefins with oxalic acid in the presence of additional CO has been reported …”
mentioning
confidence: 99%